FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN SOP PENGGUNAAN MASKER PADA PASIEN DI RUANG RAWAT INAP RS JIWA PROF.Dr. V.L. RATUMBUYSANG DI MANADO - Walewowan, Maercelina (Journal Of Community & Emergency, 2024)
Mental disorders are symptoms that are manifested through changes in the main characteristics of behavioral or psychological damage to the function. The number of positive cases of Covid-19 on Sunday 17/5 in 2021 experienced a high increase. The number of additions today is 4,394 people. So that the cumulative total of 1,877,274 people in Indonesia were confirmed positive for Covid-19. While the number of recovered cases today is 3,740 people who have tested negative for Covid-19. So, the current cumulative total in Indonesia, there are 1,630,718 people who have successfully recovered from Covid-19. The data for patients who died today is 144 people. Currently, there are 45,796 people who have died due to corona in Indonesia. Objective. Standard Operational Procedure (SOP) is a guideline or reference for carrying out work tasks in accordance with the functions and performance appraisal tools of government agencies based on technical, administrative and procedural indicators. in accordance with work procedures, work procedures and work systems in the work unit concerned. The research is known factors related to compliance with SOP on the use of masks in patients in the Inpatient Room of RSJ Prof. Dr. V. L. Ratuumbuysang Manado.. The type of research conducted is descriptive analytic data analysis used Chi-Square test with a significance value of p = 0.05. The time and place of the research, namely September 2021, this research was carried out in the Inpatient Room of RSJ Prof. Dr. V. L. Ratuumbuysang Manado The results of the study obtained that the results of the length of patient care, patient knowledge and patient attitudes had a relationship with SOP compliance for the use of masks in patients in the Inpatient Room of RS. Jiwa Prof. Dr. V.L.Ratumbuysang Manado with each P value for the length of treatment, p value 0.003, Patient Knowledge, p value 0.001 and Patient Attitude P value 0.001 The conclusion from the results of the study shows the length of care for mental patients in the inpatient room of the RSJ. Prof. Dr. V.L. Ratumbuysang Manado more than 1 year old compared to < 1 year. Knowledge of Mental Patients in the RSJ Inpatient Room. Prof. Dr. V.L. Ratuumbuysang Manado has more good knowledge than less knowledge. Compliance with SOP for the use of masks for mental patients in the RSJ Inpatient Room. Prof. Dr. V.L. Ratumbuysang Manado is more obedient than disobedient.